Cement augmentation of the Proximal Femoral Nail Antirotation (PFNA) – A multicentre randomized controlled trial. Issue 8 (August 2018) - Kammerlander, Christian; Hem, Einar S.; Klopfer, Tim; Gebhard, Florian; Sermon, An; Dietrich, Michael; Bach, Olaf; Weil, Yoram; Babst, Reto; Blauth, Michael
Abstract: Introduction: New implant designs like the Proximal Femoral Nail Antirotation (PFNA) were developed to reduce failure rates in unstable pertrochanteric fractures in the elderly. Standardized implant augmentation with up to 6 mL of polymethylmethacrylate (PMMA) cement has been introduced to enhance implant anchorage by increasing the implant-bone interface in osteoporotic bone conditions. Biomechanically, loads to failure were significantly higher with augmentation. The primary objective of this study was to compare the mobility of patients with closed unstable trochanteric fractures treated by PFNA either with or without cement augmentation. Patients and methods: A prospective multicentre, randomized, patient-blinded trial was conducted with ambulatory patients aged 75 or older who sustained a closed, unstable trochanteric fracture. Surgical fixation had to be performed within 72 h after admission. Outcomes were evaluated at baseline, during surgery, 3 to 14 days after surgery, 3 months, 6 months, and 12 months after surgery. To evaluate the primary objective, patients' walking speed was assessed by the Timed Up and Go (TUG) test. Secondary objectives included the analysis of implant migration assessed on radiographs, quality of life measured by the Barthel Index, mobility measured by the Parker Mobility Score, and complications. Results: Of 253 randomized patients, 223 patients were eligible: 105 patients were allocated to the PFNA Augmentation group and 118 to PFNA group. At 3 to 14 days after surgery, there was no statistical significant difference in mean walking speed between the treatment groups. For the secondary objectives, also no statistical significant differences were found. However, no patient in the PFNA Augmentation group had a reoperation due to mechanical failure or symptomatic implant migration compared to 6 patients in the PFNA group. Conclusions: Augmentation of the PFNA blade did not improve patients' walking ability compared to the use of a non-augmented PFNA but might have the potential to prevent reoperations by strengthening the osteosynthesis construct.